THE NUMERICAL INVERSION OF THE LAPLACE TRANSFORM IN REPRODUCING KERNEL HILBERT SPACES - Iqbal, M. (Journal of Research (Science), 2001)
In this paper we have converted the Laplace transform into an integral equation of the first kind of convolution type, which is an ill-posed problem and used a statistical regularization method to solve it. The method is applied to three examples taken from Rodriguez and Seatzu [1993]. It gives a good approximation to the true solution and compares well with the method given by Rodriguez and Seatzu [1993]. The results are shown in the Table and the diagrams.